An update on primary sclerosing cholangitis epidemiology, outcomes and quantification of alkaline phosphatase variability in a population-based cohort - Bakhshi, Zeinab; Hilscher, Moira B.; Gores, Gregory J.; Harmsen, William S.; Viehman, Jason K.; LaRusso, Nicholas F.; Gossard, Andrea A.; Lazaridis, Konstantinos N.; Lindor, Keith D.; Eaton, John E. (Journal of gastroenterology, 2020)
Background Contemporary primary sclerosing cholangitis (PSC) population-based cohorts describing the epidemiology, natural history, and long-term fluctuations in serum alkaline phosphatase (SAP) and their prognostic relevance are lacking. Therefore, we investigated the incidence and natural history of PSC and quantified SAP fluctuations among those with PSC in Olmsted County, Minnesota over the last 41 years. Methods The Rochester Epidemiology Project was used to identify 56 subjects diagnosed with PSC between 1976 and 2017 in Olmsted County. The primary endpoint ( n = 19) included liver transplantation, hepatic decompensation, and cholangiocarcinoma. Results The age- and sex-adjusted incidence of PSC (per 100,000 person years) nearly doubled from 2001 to 2017 compared to 1976–2000 (1.47; 95% CI 0.99–1.96 versus 0.79; 95% CI 0.42–1.16, p = 0.02). This increase paralleled a rise in patients with markers of a milder phenotype at the time of diagnosis: normal SAP (26.32% versus 0%, p < 0.01) and lower Mayo PSC risk score [0.36 (− 0.57 to 1.55) versus − 0.50 (− 1.25 to 0.35), p = 0.03]. Intra-individual SAP fluctuates with a median coefficient of variation of 36.20%. SAP normalization and dropping below 1.5 × upper limit of normal (ULN) occurs at a rate of 5% and 10% per year, respectively. SAP less than 1.5 × ULN was associated with a lower risk of PSC-related complications (hazard ratio 0.11; 95% CI 0.03–0.42). Conclusions The patients with PSC are increasingly being diagnosed with a milder phenotype. While a lower SAP is associated with improved outcomes, the high intra-individual variation of SAP levels calls into question the practice of using a single SAP value as a surrogate endpoint in clinical trials.